Living Hadis Tradisi Sholawat Kuntulan Di Desa Bengle Kabupaten Tegal - Arini Alfa Hani; M. Riyan Hidayat (Jurnal Studi Hadis Nusantara, 2021)
This study focuses on the practice of sholawat Kuntulan which was carried out in Bengle Village, Tegal Regency. The research is studied in depth with the living hadith approach. The purpose of this study is to reveal the meaning of the sholawat kuntulan tradition and the motives behind it. The research method used is descriptive qualitative. This research is included in the field research category, which collects data through the stages of observation, interviews, and documentation. The results show that this tradition has a philosophical meaning in every movement used. At least the meaning contained aims as a medium of da'wah to the Bengle community and preserves the traditions that have developed from the past.